Laser and Light‐Based Therapies in Inflammatory Dermatoses: A Systematic Review of Safety, Efficacy, and Adverse Effects to Inform Cosmetic Use - Carli Tucci; Richard Li; Farida Ettefa; Maressa C. Criscito; Lisa O. Akintilo (Lasers in Surgery and Medicine, 2026)
ABSTRACT Objectives Laser and light‐based therapies are widely used in dermatology, yet patients with inflammatory dermatoses are often excluded from cosmetic procedures due to concerns for disease exacerbation. This systematic review evaluated the safety and efficacy of these modalities to inform their use. Methods A PRISMA‐guided search of PubMed, Embase, ClinicalTrials.gov, and Scopus from inception through March 1, 2026 identified studies of adults with psoriasis, atopic dermatitis, lichen sclerosus, lichen planus pigmentosus, frontal fibrosing alopecia, or cutaneous sarcoidosis treated with laser or light‐based therapies. Eligible studies reported clinical outcomes and adverse events; reviews and studies without attributable outcomes were excluded. Risk of bias was assessed qualitatively, and results were synthesized descriptively. Results Fifty‐seven studies including over 900 patients were analyzed, with the strongest evidence in psoriasis and lichen sclerosus. Across conditions and device types, therapies consistently demonstrated clinical improvement and were generally well tolerated. Adverse effects were predominantly localized and transient, including erythema, edema, blistering, and pigmentary changes. Serious adverse events were rare, with only isolated cases of koebnerization or disease worsening reported. Limitations include heterogeneity and predominance of small or non‐randomized studies. Conclusions These findings suggest that, in appropriately selected patients, laser and light‐based therapies are safe and do not consistently precipitate disease exacerbation.